Penggunaan Aplikasi Hornet Terhadap Pola Komunikasi Penyuka Sesama Jenis (GAY) di Kota Tegal - Fajar Maulana Iqbal; Ike Desi Florina; Diryo Suparto (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
The aim of this research is to study two things: how gay people use the Hornet application in Tegal City and how this application impacts gay people. This research is a phenomenological study. Apart from that, the data collection method uses first observation, in-depth interviews with five main informants—gays—using the Hornet application, and collecting documents relevant to the research objectives. The research results show that several communication patterns are used in interacting with the hornet application: 1) communication patterns to seek friendship; 2) communication patterns to seek relationships; 3) communication patterns for seeking meetings; 4) communication patterns using special language or nonverbal language; 5) communication patterns that use stimuli; and 6) communication patterns that determine behavior when given stimuli. According to the five informants, the Hornet application is relevant for gay groups in terms of openness about their sexual orientation.